Urgensi manajemen risiko reputasi terhadap kepercayaan nasabah bank syariah di indonesia - Kamarullah, Khalifaturrahman (Maliki Interdisciplinary Journal, 2025)
In the competitive financial industry, reputation is a vital intangible asset, especially for Islamic banks that uphold the principles of fairness, honesty, and Sharia compliance. Reputation risks can arise from various internal and external factors, including ethical violations, the spread of negative information on social media, and low Islamic financial literacy. The impacts include a decline in trust, customer loyalty, and financial and social losses. Using a literature review approach, this study highlights the importance of reputation risk management strategies that include the stages of identification, assessment, mitigation, and monitoring. The role of public communication, the Sharia Supervisory Board, and the principles of Good Corporate Governance in strengthening public trust is also emphasized. Despite facing challenges related to digitalization and low public understanding of the Sharia system, Islamic banks have a significant opportunity to build an excellent reputation by emphasizing Islamic values and integrity. The results of this study confirm that reputation risk management must be an integral part of the sustainable management strategy of Islamic banks.